Pengaruh Manajemen Risiko Korporasi, Perputaran Persediaan, Profitabilitas, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Hermanto; Jessica Margarena (Jurnal Informatika Ekonomi Bisnis, 2023)
This test aims to identify the correlation between corporate risk management, inventory turnover, profitability, and firm size with firm value. This study uses data collected from the financial statements of the food and beverage sub-sector listed on the Indonesia Stock Exchange during the research period 2016-2022. The purposive sampling method was carried out with exploratory steps, where this study took 63 samples from a total of 9 companies and reduced after testing several criteria to 6 companies so that the total sample studied was 42 samples over a 7-year period in accordance with the research criteria. The results showed that corporate risk management has no correlation to firm value, inventory turnover has no effect on firm value, while profitability has a positive influence on firm value, and firm size has no correlation to firm value.